AFIKSASI BAHASA MELAYU DALAM KOBA SASTRA LISAN ORANG RIAU (Dalam Dialek Daerah Rokan Hilir) - Laksmawati, Dewi; ', Charlina; Faizah, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study discusses the affixation language of Malay dialect in Koba Literature Oral People of Riau (in districts Rokan Hilir). This descriptive research used qualitative approach which aimed to describe the uniqueness affixation language of Malay in Koba Literature Oral People of Riau (in dialect districts Rokan Hilir). This research included into written data from book Koba Literature Oral People of Riau (in dialect districts Rokan Hilir) works Ediruslan Pe Amanriza, Tenas Effendi, dan Sudarno Mahyudin. The data obtained with reading the book Koba Literature Oral People of Riau (in dialect districts Rokan Hilir) works Ediruslan Pe Amanriza, Tenas Effendi, dan Sudarno Mahyudin. Then marks a word wich has affix in the book Koba Literature Oral People of Riau (in dialect districts Rokan Hilir) works Ediruslan Pe Amanriza, Tenas Effendi, dan Sudarno Mahyudin. Based on the results of research, afiksasi language of Malay in Koba Literature Oral People of Riau (in dialect districts Rokan Hilir) has five affix that are, /prefix/, /sufix/, /infix/, /konfiks/, and /combined affix/. The result of this research is a form of documentation affixation language of Malay in Koba Literature Oral People of Riau (in dialect districts Rokan Hilir).Keywords: affixation language of Malay and Koba Literature Oral People of Riau (in dialect districts Rokan Hilir).